LEARNING MANAGEMENT IN THE DEVELOPMENT OF STUDENTS' SOCIAL ABILITY AT RA KHOLAFIYAH SYAFIIYAH - Fatin, Fadiyah Tutik; Ainol, Ainol; DP, Terza Travelancya (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This journal discusses the importance of learning management in developing students' social skills. RA Kholafiyah Syafiiyah as a school that organizes Islamic education prioritizes the development of students' social skills. In this article, the author explains how good learning management can help students improve their social skills. The article also discusses various management learning theories that can be applied in developing students' social skills. The results of the study show that good learning management can help students improve their social skills. Learning management strategies such as developing social-based learning models, increasing interaction between students, and group assignments can help students improve their social skills. The conclusion of this article is that learning management plays an important role in developing students' social skills. RA Kholafiyah Syafiiyah as a school that has a strong vision and mission in developing students, must implement effective and good learning management to help students improve their social skills.